Impact of Educational Intervention in Knowledge of Infection Prevention and Control among healthcare professionals in Nepal - Pradhan, Sait Kumar; Shrestha, Sweta (Journal of Business and Social Sciences, 2018)
Background: Health care-associated infection (HCAI) affects the mortality and morbidity of inpatients worldwide. Nepal is a developing country in which HCAI pose a major problem in terms of patient safety. Improper and inadequate knowledge about HCAI among health care workers is responsible for majority of nosocomial infections resulting in prolonged illness. Thus this study was designed to assess the level of knowledge of infection control among nurses and pharmacists. Methods: A pre and post interventional study was conducted in 22 participants using a self-administered questionnaire which included queries on hand hygiene strategies, cross contamination sources and aseptic services. Each correct answer was scored as 1 and an incorrect answer was scored as zero. The total score for each individual was calculated before and after the intervention which was compared using the Paired t test at 95% confidence interval. Result: 81.8% of the participants possessed a good knowledge on infection prevention and control practices which increased to 100% after intervention. The difference in knowledge score before and after the workshop was found to be statistically significant (p=0.034). Previous training and duration of work experience was found to be correlated with the knowledge score whereas the other independent variables had no association with the knowledge score. Conclusion: Educational intervention has a positive impact in the knowledge level of the healthcare professionals in infection and prevention control.